Inovasi Pengelolaan Sumber Daya Pendidikan Dalam Meningkatkan Daya Saing Lembaga Pendidikan - Ahya Alfiyan Nur; Istikomah Kusuma Ningrum; Santy Santy; Akhmad Ramli (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze educational resource management innovation in enhancing the competitiveness of educational institutions in Samarinda City through data-driven managerial transformation, adaptive curriculum integration, integrated school optimization, and collaborative governance. The study employed a qualitative descriptive approach. The research sites included SMA Negeri 10 Samarinda, the Loa Bakung Integrated School Complex (SD Negeri 028 Samarinda, SMP Negeri 16 Samarinda, and SMA Prestasi Samarinda), and Sekolah Rakyat Terintegrasi (SRT) 24 Samarinda. Data were collected through observation, in-depth interviews, and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing and verification. Data credibility was ensured through source triangulation, technique triangulation, and member checking. The findings reveal that data-driven managerial transformation improves decision-making effectiveness and the efficiency of educational resource management. Adaptive curriculum integration enhances the relevance of learning to technological developments, regional needs, and students' characteristics. The optimization of integrated schools through a resource-sharing approach enhances the efficient utilization of infrastructure, teaching staff, and educational programs, while collaborative governance fosters synergy among local governments, schools, parents, communities, and the private sector in improving educational quality. This study proposes an integrated educational resource management innovation model that combines these four strategic components to enhance institutional competitiveness. The model provides both theoretical and practical contributions to strengthening sustainable educational management at the regional level.